2008
DOI: 10.1007/s11255-008-9469-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting functioning and well-being in older CKD patients: review of recent evidence

Abstract: Osteoporosis, falls, sleep difficulty, cognitive impairment, and depressed mood are major clinical concerns in the geriatric population that are physiologically and psychologically based and are often interrelated. All of these issues have implications for patients' daily functioning and quality of life (QOL). This review synthesizes recent evidence about these prominent issues in geriatric care and related implications for care of older patients with chronic kidney disease (CKD). Recent evidence about pre-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 56 publications
(77 reference statements)
0
29
0
2
Order By: Relevance
“…5,9,10,12,18,20,24 The specifi c dimensions of KDQOL-SF with the lowest mean scores were effects of kidney disease on daily life, burden of kidney disease, work status and patient satisfaction. The generic dimensions of SF-36 with the lowest scores were physical functioning, role-physical, and overall health rating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,10,12,18,20,24 The specifi c dimensions of KDQOL-SF with the lowest mean scores were effects of kidney disease on daily life, burden of kidney disease, work status and patient satisfaction. The generic dimensions of SF-36 with the lowest scores were physical functioning, role-physical, and overall health rating.…”
Section: Discussionmentioning
confidence: 99%
“…Mapes et al 15 concluded that the PCS was the component of QoL most strongly associated with mortality. According to Kutner,10 although physical health status is compromised in elderly patients on dialysis, their mental health status is relatively preserved. There are no studies in Brazil on the impact of PCS and MCS on mortality in elderly patients on hemodialysis and further studies are needed to explore this relationship.…”
Section: Deoreomentioning
confidence: 99%
“…This may be alleviated with the increase of knowledge related to gerontology, as well as supporting and helping issues of well-being in elderly people (Kutner, 2008). The ageing of society represents a socio-demographic change which has been increasing in recent decades.…”
Section: Ageing and Quality Of Life In Western Countriesmentioning
confidence: 99%
“…Studies suggest that .45% of elderly patients undergoing dialysis have one or more falls per year (5,6). Falls are an important risk factor for fractures, future falls, and death in geriatric populations.…”
Section: Fallsmentioning
confidence: 99%